Differences in Intrinsic Brain Abnormalities Between Patients With Left- and Right-Sided Long-Term Hearing Impairment - Xie, Xiaoxiao; Liu, Yongbo; Han, Xiaowei; Liu, Pei; Qiu, Hui; Li, Junfeng; Yu, Huachen (Frontiers in Neuroscience, 2019)
Unilateral hearing impairment is characterized by asymmetric hearing input, which causes bilateral unbalanced auditory afferents and tinnitus of varying degrees. Long-term hearing imbalance can cause functional reorganization in the brain. However, differences between intrinsic functional changes in the brains of patients with left- and those with right-sided long-term hearing impairments are incompletely understood. This study included 67 patients with unilateral hearing impairments (left-sided, 33 patients; right-sided, 34 patients) and 32 healthy controls. All study participants underwent blood oxygenation level dependent resting-state functional magnetic resonance imaging and T1-weighted imaging with three-dimensional fast spoiled gradient-echo sequences. After data preprocessing, fractional amplitude of low frequency (fALFF) and functional connectivity (FC) analyses were used to evaluate differences between patients and healthy controls. When compared with the right-sided hearing impairment group, the left-sided hearing impairment group showed significantly higher fALFF values in the left superior parietal gyrus, right inferior parietal lobule, and right superior frontal gyrus, whereas it showed significantly lower fALFF values in the left Heschl's gyrus, right supramarginal gyrus, and left superior frontal gyrus. In the left-sided hearing impairment group, paired brain regions with enhanced FC were the left Heschl's gyrus and right supramarginal gyrus, left Heschl's gyrus and left superior parietal gyrus, left superior parietal gyrus and right inferior parietal lobule, right inferior parietal lobule and right superior frontal gyrus, and left and right superior frontal gyri. Negative correlations were present between the FC of the paired brain regions and the duration and pure tone audiometry in the left Heschl's gyrus and right supramarginal gyrus in the left-sided hearing impairment group, the FC of the paired brain regions and duration in the left Heschl's gyrus and left superior parietal gyrus, and the FC of the paired brain regions and pure tone audiometry in the right inferior parietal lobule and right superior frontal gyrus in the right-sided hearing impairment group. The intrinsic reintegration mechanisms of the brain appeared to differ between patients with left-sided hearing impairment and those with right-sided hearing impairment, and the severity of hearing impairment was associated with differences in functional integration in certain brain regions.